Undergraduates entrepreneurial intention: Holistic determinants matter - Tan Owee Kowang; Siti Zulaiha Binti Abdulah Apandi; Ong Choon Hee; Goh Chin Fei; Mohd Saiful Izwaan Saadon; Mohamad Rosni Othman (Institute of Advanced Engineering and Science, 2021)
The role of entrepreneurship in job creation and unemployment reduction is well established by prior studies. Hence, one of the ways to address the unemployment issue among young graduates in Malaysia is to explore how entrepreneurial intention could be embraced into the broader context of the country's education system. Empirical research found that prior studies on entrepreneurship education in Malaysia tends to focus on reviewing educational policies, issue and challenges. The concept of the entrepreneurial intention determinants beyond entrepreneurial education remains ambiguous. Hence, this study advances the discussion in entrepreneurship education by reviewing determinants for entrepreneurial intention from holistic perspective by integrating Model of Personality Traits and the theory of planned behavior (TPB). Five determinants for entrepreneurial intention are identified from literature review, which are entrepreneurship attitude, subjective norm, behavior control, entrepreneurship education and personality traits. The study is quantitative based, 360 questionnaires were distributed to the undergraduates from three faculties of a public university in Malaysia, with 199 responded. Data was analyzed via Pearson correlation and ANOVA analysis. Finding from the study suggested all the five entrepreneurial determinants are significantly correlated with entrepreneurial intention, and there is no significant difference on entrepreneurial intention based on faculty. However, one of the remarkable finding is Entrepreneurship Education is viewed as determinant with the lowest correlation coefficient with entrepreneurial intention. The implication of this finding is perhaps the content of entrepreneurial education shall emphasize on cultivating students’ entrepreneurial attitude, behavioral and personality rather than the theoretical part of entrepreneurial and entrepreneurship.